Bovine Interferon Lambda Is a Potent Antiviral Against SARS-CoV-2 Infection in vitro - Cardoso, Nancy Patricia; Mansilla, Florencia Celeste; Benedetti, Estefanía; Turco, Cecilia Soledad; Barone, Lucas José; Iserte, Javier Alonso; Soria, Ivana; Baumeister, Elsa; Capozzo, Alejandra Victoria (Frontiers in Veterinary Science, 2020)
Interferon lambda (IFN-λ) is an antiviral naturally produced in response to viral infections, with activity on cells of epithelial origin and located in the mucosal surfaces. This localized activity results in reduced toxicity compared to type I IFNs, which receptors are ubiquitously expressed. IFN-λ has been effective in the therapy of respiratory viral infections, playing a crucial role in potentiating adaptive immune responses that initiate at mucosal surfaces. Human IFN-λ has polymorphisms that may cause differences in the interaction with the specific receptor in the human population. Interestingly, bovine IFN-λ3 has an in silico-predicted higher affinity for the human receptor than its human counterparts, with high identity with different human IFN-λ variants, making it a suitable antiviral therapeutic candidate for human health. Here we demonstrate that a recombinant bovine IFN-λ (rbIFN-λ) produced in HEK-293 cells is effective in preventing SARS-CoV-2 infection of VERO cells, with an inhibitory concentration 50% (IC50) between 30 and 50 times lower than that of human type I IFN tested here (α2b and β1a). We also demonstrated the absence of toxicity of rbIFN-λ in human PBMC and the lack of proinflammatory activity on these cells. Altogether, our results show that rbIFN-λ is as an effective antiviral potentially suitable for COVID-19 therapy. Among other potential applications, rbIFN-λ could be useful to preclude virus dispersion to the lungs and/or to reduce transmission from infected people. Moreover, and due to the nonspecific activity of this IFN, it can be potentially effective against other respiratory viruses that may be circulating together with SARS-CoV-2.